Simultaneous Boost of Power Factor and Figure‐of‐Merit in In–Cu Codoped SnTe. Issue 36 (24th July 2019) - Guo, Fengkai; Cui, Bo; Geng, Huiyuan; Zhang, Yang; Wu, Haijun; Zhang, Qian; Yu, Bo; Pennycook, Stephen J.; Cai, Wei; Sui, Jiehe
Abstract: Significantly enhanced thermoelectric performance is achieved for eco‐friendly SnTe by a coorperative effect between a dopant resonant energy level and interstitial defects. By manipulating the band structure through indium doping, the Seebeck coefficient is remarkably improved, leading to an enhanced power factor, with a high level of ≈29 µW cm −1 K −2 at 873 K. Lattice thermal conductivity is sharply reduced, approaching the amorphous limit, through the strong phonon scattering induced by multiple scales of Cu2 Te nanoprecipitates, as well as Cu interstitials, leading to a high ZT value of ≈1.55 at 873 K. Abstract : Resonant level and interstitials simultaneously boost the PF and ZT values of SnTe . In–Cu codoped SnTe possesses a high ZT value of ≈1.55, a relatively high power factor of ≈29 µW cm −1 K −2 at 873 K, and average power factor of ≈22 µW cm −1 K −2 from 300 to 873 K.